Stigma experience and coping strategies in stroke survivors: a qualitative study - Song, Lina; Sun, Xinbo; Li, Chengxia; Li, Bing; Jing, Lijie; Jing, Xuebing (Frontiers in Psychology, 2025)
AimTo investigate the true experiences of stigma and changes in stroke survivors and explore how they manage their symptoms.BackgroundStroke is a serious disease that threatens human health with increasing mortality and disability rates. Declining self-care ability and excessive external dependence can easily lead to stigma. However, there is a lack of studies on real stigma experiences and coping styles among stroke survivors.DesignA descriptive qualitative study.MethodsFourteen participants were recruited across inpatient stroke settings in China. Semi-structured face-to-face interviews were conducted with participants to collect data. Audio-recorded data were transcribed. The data were analyzed using the seven-step Colaizzi method for phenomenological analysis, adhering to the principles of Phenomenological research methodology. The study adheres to SRQR EQUATOR checklist.FindingsFourteen semi-structured interviews were conducted, revealing three main themes and ten sub-themes: (1) Non-adaptive emotion regulation in response to stigma, including sub-themes of remorse, shame, sadness, perceived disaster, depression, and reduced self-worth; (2) Adaptive emotion regulation in response to stigma, including positive reappraisal, positive adjustment, acceptance, and support systems; (3) Origins of stigma, including sources such as relatives, friends, oneself, and medical staff.ConclusionThe findings have the potential to inform the development and implementation of strategies to reduce the experience of stigma in early-stage clinical settings. Medical professionals must prioritize the comprehensive examination of genuine instances of stigma encountered by stroke survivors. Timely identification of stigma is imperative to mitigate the risk of patients adopting inaccurate beliefs and maladaptive coping mechanisms post-stroke. Strategies aimed at diminishing stigma should consider personal, familial, policy-related, societal, institutional, and environmental dimensions.